2019
DOI: 10.1111/bju.14751
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival outcomes in patients with upper urinary tract urothelial carcinoma diagnosed with variant histology and treated with nephroureterectomy

Abstract: Objective To evaluate the incidence and survival outcomes of histological variants of upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU). Materials and Methods We retrospectively analysed data from 1610 patients treated with RNU for clinically non‐metastatic UTUC between 1990 and 2016 in several centres participating in the UTUC Collaboration. Histological variants were classified as micropapillary, squamous, sarcomatoid and other, including other rare variants (<10 cases for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
2
24
1
Order By: Relevance
“…A previous study found that the incidence of histologic variation in UTUC was approximately 10%. Micropapillary and sarcomatoid variations may lead to poor oncology outcomes ( 30 ). Another study also suggested that the micropapillary variation often predicts a poor biological behavior in invasive urothelial carcinoma of the bladder ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that the incidence of histologic variation in UTUC was approximately 10%. Micropapillary and sarcomatoid variations may lead to poor oncology outcomes ( 30 ). Another study also suggested that the micropapillary variation often predicts a poor biological behavior in invasive urothelial carcinoma of the bladder ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study 14 patients were confirmed only by ureteroscopy and biopsy, and they have limitations in upper tract disease. Previous studies showed that micropapillary and sarcomatoid variants were associated with poorer oncological outcomes, and molecular markers such as human epidermal growth factor receptor−2 (HER2) is considered to be a potential prognostic and therapeutic marker in patients with upper tract urothelial carcinoma ( 21 , 22 ). In our study, no patients with micropapillary and sarcomatoid variants were found.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Meanwhile, the rest of the common malignancies of the urinary system, such as kidney, bladder, and upper urinary tract cancers, also pose a serious threat to human health. [5][6][7] Although surgical techniques and medical therapies (chemotherapy, radiotherapy, immunotherapy and so on) have been rapidly developed in the last ten years, the ve-year survival rate of patients with urinary system cancers is still not optimistic. [8,9] Therefore, especially useful new biomarkers that could be helpful for the diagnosis, evaluation and even improvement of prognosis in urinary system cancers should be identi ed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%